2010
DOI: 10.1891/1946-6560.1.3.286
|View full text |Cite
|
Sign up to set email alerts
|

A Closer Look at Men Who Sustain Intimate Terrorism by Women

Abstract: Over 30 years of research has established that both men and women are capable of sustaining intimate partner violence (IPV) by their opposite-sex partners, yet little research has examined men's experiences in such relationships. Some experts in the field have forwarded assumptions about men who sustain IPV–for example, that the abuse they experience is trivial or humorous and of no consequence and that, if their abuse was severe enough, they have the financial and psychological resources to easily leave the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
151
2
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(168 citation statements)
references
References 48 publications
(61 reference statements)
11
151
2
4
Order By: Relevance
“…En cuanto al sexo del agresor la literatura científica ha apuntado que son las mujeres quienes suelen ejercer más violencia psicológica que la física, ocasionando así daños emocionales, psicológicos y sociales en sus parejas (Hines & Douglas, 2010;Lysova, 2007). Sin embargo a últimas fechas algunas investigaciones han observado la presencia de este tipo de agresión cometida tanto por hombres como por mujeres (Dietz & Jasinski, 2003), sin importar edades o contextos (Kaukinen, Gover, & Hartman, 2012).…”
Section: Violencia Psicológica En El Noviazgounclassified
See 1 more Smart Citation
“…En cuanto al sexo del agresor la literatura científica ha apuntado que son las mujeres quienes suelen ejercer más violencia psicológica que la física, ocasionando así daños emocionales, psicológicos y sociales en sus parejas (Hines & Douglas, 2010;Lysova, 2007). Sin embargo a últimas fechas algunas investigaciones han observado la presencia de este tipo de agresión cometida tanto por hombres como por mujeres (Dietz & Jasinski, 2003), sin importar edades o contextos (Kaukinen, Gover, & Hartman, 2012).…”
Section: Violencia Psicológica En El Noviazgounclassified
“…De ese modo se esperaba que los participantes señala-ran haber sufrido violencia psicológica (Hines & Douglas, 2010), física (Rey, 2008) además de haber sufrido violencia sexual (Chávez et al, 2009) por parte de su pareja durante el noviazgo. Además era esperable que ellos manifestaran haber sufrido conductas de ciber-violencia por parte de sus parejas (Velázquez, 2013).…”
Section: Ciber-violencia En El Noviazgounclassified
“…Some researchers have suggested that victimized males face a different set of challenges than victimized females (e.g., Hines & Douglas, 2009, 2010a, 2010b and that studies of battered females will not suffice in providing a theoretical framework for understanding male victimization (e.g., George, 1994). Hines and Douglas (2009) argued that societal expectations of male dominance and the potentially greater stigma faced by male victims will likely make it more difficult to identify and treat targeted males and aggressive females (see also Gilbert, 2002).…”
mentioning
confidence: 99%
“…An example of this is that for a man to be labelled 'victim' by a female perpetrator may be threatening to his sense of masculinity (Anderson, 2005). Also, male victims of intimate partner violence by female partners are often reluctant to seek help because they are afraid of not being taken seriously, not being believed, or being seen as the main perpetrator of violence (Hines and Douglas, 2010a;Nybergh, 2014). Social reluctance to see women as perpetrators of violence is also found in the way female perpetrators of intimate partner violence are sometimes explained and understood as victims of previous violence, in childhood or in relation to partners.…”
Section: Gender and Interpersonal Violencementioning
confidence: 99%